Purinergic signal transduction and metabolic regulation by ENTPD5 and ENTPD6 - Qi, Yihang; Li, Xuefei; Song, Xinyu; Wei, Wenyi; Ghiran, Ionita; Robson, Simon C. (Frontiers in Endocrinology, 2026)
ENTPD5 and ENTPD6 are members of the CD39-ectonucleoside triphosphate diphosphohydrolase (CD39-ENTPD) family, which play an important role in modulating the purinergic signaling pathway. Most of the knowledge in this area has been obtained by studying CD39/ENTPD1, the prototype member of this family, and evaluating the translational potential by either treating inflammation directly with recombinant proteins or by using antagonists to elicit immune responses in cancer. ENTPD5 and ENTPD6, “orphan-type” ectonucleotidases, are understudied to date, although both are expressed at high levels in various tissues, where they appear involved in regulating signal transduction, cellular energy, and metabolism. ENTPD5 is abnormally overexpressed in several types of malignancies, including prostate, liver, lung, and ovarian cancers. ENTPD5 appears to promote protein glycosylation and folding in part by regulating UDP and UMP levels, thereby enhancing the survival and proliferation of somatic or cancer cells. As such, ENTPD5 has been considered a potential proto-oncogene and a therapeutic target in cancer treatment. In contrast, despite comparable functionality, the related ENTPD6 shows relatively stable expression across tissues in both normal and pathological conditions, with specific roles in cancer yet unclear. This review provides a comprehensive overview of these two understudied ectoenzymes, detailing their shared molecular structures and control of purinergic signal transduction. In addition, we explore different patterns of tissue and organelle expression of these ecto-enzymes and propose relevance to the modulation of cellular metabolism, as would be important in cancer. We review the sometimes conflicting evidence from experimental animal models and propose potential future clinical applications. This review offers insights into the roles of this distinct duo of ENTPD family members to support future basic and translational research in this field.